On application of heat-conductive plastics in LED technology - Trofimov, Yu.V.; Lishik, S.I.; Pershukevich, P.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
A comparative analysis of the characteristics of heat-conducting plastic was
performed. The results of the thermal measurements of two of the same type 3W LED
modules installed on heat sink with the same area of heat-dissipating surface made of
aluminum and heat-conducting polymer have been presented. It has been shown that the
overheating of LED module mounted on the heat-conducting polymer heat sink is
2…3 °С higher than that on the aluminum heat sink (thermal conductivity is 20 times
higher). The ranges of applicability of the heat-conducting plastics in LED technology
have been determined.